Combining lecture-based and team-based learning to improve clinical immunology practice effects in the laboratory department of a teaching hospital in China - Ye, Ting; Wan, Hong; Cheng, Song; Quan, Jing; Zhou, Jie; Deng, Jian; Dai, Bizhen; Yang, Mingxue (Pacific International Journal, 2024)
Objectives: In order to cope with the severe situation of the current COVID-19 epidemic and to provide better quality medical staffs for the Chinese medical system, as well as to promote the continuous development of clinical laboratory medicine towards standardization, normalization and technical automation. The application value of the lecture-based learning (LBL) and team-based learning (TBL) dual-track mode for internship in the clinical immunology subgroup of the laboratory department was evaluated in conjunction with the current undergraduate education mode of clinical laboratory technology in China, to provide a more efficient method for enhancing the comprehensive ability of interns in the laboratory department. Methods: A total of 61 laboratory interns from the grade 2017 of Southwest Medical University in China were collected and randomly divided into two groups: A and B. The group A adopted the traditional LBL teaching mode, and group B used the LBL-TBL dual-track teaching mode. The students' comprehensive abilities such as theoretical knowledge and experimental skills under the teaching models were compared. And finally the teaching effect was evaluated by theoretical assessment and questionnaire. Results: The satisfaction rate of group B was remarkably higher than that of group A in terms of analyzing skills, problems-solving ability and clinical operation (P < 0.05). There was no significant difference between the two groups involving in theoretical achievement levels (P > 0.05), but group B had a greater satisfaction rate than group A for enhancing theoretical knowledge acquisition. Conclusions: The LBL-TBL dual-track teaching mode plays a positive role for the internship in the laboratory department, which helps to improve the independent learning capability, analyzing skills and problems-solving ability. The LBL-TBL dual-track teaching method is worth further promotion in clinical immunology practice of the laboratory department.